2016
DOI: 10.1002/ptr.5650
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin, a Plant-Derived Compound, Exhibits Antifungal Combinatory Effect with Amphotericin B againstCandida albicansClinical Isolates and Anti-hepatitis C Virus Activity

Abstract: Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), the major active constituent of Plumbago indica L., has been shown to be effective against a wide range of infectious microbes. In this study, plumbagin has been evaluated in vitro for its antifungal combinatory effect with amphotericin B against Candida albicans (C. albicans) clinical isolates and anti-hepatitis C virus (HCV) activity. Antifungal activity was determined by broth microdilution method, and combinatory effect was evaluated by checkerboard assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 35 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…The MIC of TCH-1140 and TCH-1142 against ATCC90029 was 1.5 µM (0.32 µg/ml) and 1.2 µM (0.31 µg/ml), respectively. These values were greatly lower than the other naphthoquinone derivatives reported earlier such as 2-methyl-5-hydroxynaphtho[2,3-b]furan-4,9-dione (2-8 µg/ml), phenanthrenequinone (60 µg/ml), 2-[iodomethyl]-2,3-dihydronaphtho[2,3-b]furan-4,9-dione (12 µg/ml), and plumbagin (8 µg/ml) (Nagata et al, 1998;Neto et al, 2014;Rejiniemon et al, 2014;Hassan et al, 2016), although the C. albicans strains used were different among the different studies. This suggested the potent antifungal activity of the naphthofuranquinones developed in this work.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The MIC of TCH-1140 and TCH-1142 against ATCC90029 was 1.5 µM (0.32 µg/ml) and 1.2 µM (0.31 µg/ml), respectively. These values were greatly lower than the other naphthoquinone derivatives reported earlier such as 2-methyl-5-hydroxynaphtho[2,3-b]furan-4,9-dione (2-8 µg/ml), phenanthrenequinone (60 µg/ml), 2-[iodomethyl]-2,3-dihydronaphtho[2,3-b]furan-4,9-dione (12 µg/ml), and plumbagin (8 µg/ml) (Nagata et al, 1998;Neto et al, 2014;Rejiniemon et al, 2014;Hassan et al, 2016), although the C. albicans strains used were different among the different studies. This suggested the potent antifungal activity of the naphthofuranquinones developed in this work.…”
Section: Discussionmentioning
confidence: 66%
“…Naphthofuranquinones are a quinine subclass possessing some bioactivities such as antimicrobial, anti-inflammatory, and antitumor potencies (Tsang et al, 2018). Previous studies (Gershon and Shanks, 1975;Nagata et al, 1998;Neto et al, 2014;Rejiniemon et al, 2014;Hassan et al, 2016;Xie et al, 2016) demonstrated that naphthofuranquinones showed the capability to eradicate Candida species. We prepared a series of naphthofuranquinone derivatives, which displayed anti-inflammatory and anticancer activities (Tseng et al, 2009;Chien et al, 2010;Tsai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ROS inducers like quinones have been previously shown to induce RNA degradation of the RNA viruses, Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV) ( Hassan et al, 2016 ; Min et al, 2002 ). Single-stranded RNAs are vulnerable to damages in comparison with other macromolecules like DNA/protein; moreover, as endogenous RNAs are synthesized in multiple copies, cells could afford to lose the damaged RNAs, which are transient nucleic acids, through degradation mediated by RNA surveillance mechanisms ( Chang et al, 2008 ; Nunomura et al, 1999 , 2002 bib_Nunomura_et_al_2002 bib_Nunomura_et_al_1999 ).…”
Section: Insights Into Targeting Viral Rna By Ros Inducersmentioning
confidence: 99%
“…On the analysis of intracellular HCV RNA by RT-PCR, it was demonstrated that Plumbagin inhibited the HCV replication at an IC50 (half-maximal inhibitory concentration) of 0.57 μM/L and a CC50 (50% cytotoxic concentration) of 30.65 μM/L, thus resulting in a selectivity index (SI) of 53.7, in comparison with the standard antiviral drug, telaprevir, which exhibited an SI of 2127. Plumbagin administration also caused an enhanced expression of anti-HCV cellular host factor hA3G protein, a cytidine deaminase and a reduction in NS3 HCV non-structural protein levels to compromise the viral replication machinery, in a dose-dependent manner, more effectively when compared with telaprevir ( Hassan et al, 2016 ). Further, studies were carried out on extracts from Plumbago indica (a natural source of Plumbagin) and Allium sativum (commonly known as garlic) to analyze their antiviral properties against Influenza A (H1N1) pdm09 employing two principles, which are either simultaneous exposure assays (to analyze if the compound inhibits viral adsorption onto the cell surface receptors) or the post-exposure treatment assays (to analyze if the compound inhibits viral replication inside the host cells or prevent budding from the infected cells).…”
Section: Our Perspective On Prospective Inhibition Of Sars-cov-2 By Pmentioning
confidence: 99%
“…Plumbagin has demonstrated several biological activities including anticancer [ 59 ], anti-inflammatory and antimicrobial [ 60 ]. Hassan et al reported a dose-dependent effect of plumbagin on HCV lifecycle by the infection of Huh-7.5 cells with the full-length HCV FL-J6/JFH/JC1 for 6 h and treatment with plumbagin for 96 h. The intracellular HCV RNA was quantified by real-time PCR and plumbagin demonstrated an IC50 value of 0.57 μM/L and SI = 53.7 [ 61 ]. The authors analyzed the expression of non-structural protein NS3 of HCV and the cellular protein hA3G, a cytidine deaminase that was described as a host factor with anti-HCV activity [ 62 ].…”
Section: Plant-derived Compounds With Anti-hcv Propertiesmentioning
confidence: 99%